2015
DOI: 10.1590/0004-282x20150089
|View full text |Cite
|
Sign up to set email alerts
|

The influence of enriched environment on spatial memory in Swiss mice of different ages

Abstract: The objective of this study was to evaluate the influence of enriched environment on spatial memory acquisition in mice of three different age groups. Weanling, young, and young adult female Swiss mice were housed in a standard control or enriched environment for 50 days, and their spatial memory was tested with the Morris Water Maze. We did not observe an experimental effect for spatial memory acquisition, and there was neither an effect of time of analysis nor an interaction between experimental group and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This lower locomotor activity has been also interpreted as an enhanced habituation to the novelty of the testing environment [ 93 ]. In addition, enriched rats and mice were found to spend more time in the open arms in the elevated plus maze (EPM), and showed lower amounts of defensive burying and less defensive behavior when in close proximity to a predator, also suggesting reduced anxiety [ 94 , 12 ]. Finally, we found that enriched aged rats showed a reduced emotional reactivity to the conflict approach/avoidance and an improvement in decision making in the elevated-zero maze (EZM) test.…”
Section: Resilience Environmental Enrichment and Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…This lower locomotor activity has been also interpreted as an enhanced habituation to the novelty of the testing environment [ 93 ]. In addition, enriched rats and mice were found to spend more time in the open arms in the elevated plus maze (EPM), and showed lower amounts of defensive burying and less defensive behavior when in close proximity to a predator, also suggesting reduced anxiety [ 94 , 12 ]. Finally, we found that enriched aged rats showed a reduced emotional reactivity to the conflict approach/avoidance and an improvement in decision making in the elevated-zero maze (EZM) test.…”
Section: Resilience Environmental Enrichment and Agingmentioning
confidence: 99%
“…However, aged rats exposed to EE for 8 weeks have shown an increase in the extracellular levels of GABAergic compared to standard-housing condition rats [ 133 ]. Related to this, our group found that EE increased the expression of parvalbumin-positive cells in some medial prefrontal regions, such as cingulate and prelimbic cortices involved in the regulation of stress-related behaviors [ 12 ].…”
Section: Resilience Environmental Enrichment and Agingmentioning
confidence: 99%
See 1 more Smart Citation